Handbook of sport psychology - Tenenbaum, Gershon; Eklund, Robert C. (Robert Charles) 1958- (Wiley, 2020)
In the preface to the 1st Edition of the Handbook of Sport Psychology (published by Macmillan), Singer, Murphey, and Tennant (1993) contemplated on issues relating to its structure, topical coverage, authorship, and geographic representation. They found it particularly challenging to distinguish among sport psychology, motor behavior, motor learning, motor control, and motor development while considering the contents and issues to be included in the seminal edition. Their expressed desire was also to provide coverage of research on applied issues, mainly mental interventions, which they claimed must be scientifically/evidenced based. The overall focus was aimed at providing the state of the art research in the relatively new but growing domain, while also acknowledging and highlighting conceptual and methodological issues and limitations to be addressed to facilitate further advancement. The 1st Edition of the Handbook of Sport Psyhcology consisted of 44 chapters embedded within 11 sections"--